2009
DOI: 10.1111/j.1742-7843.2009.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Effect of the Psychosocial Working Environment on Physiological Changes in Blood and Urine

Abstract: The aim of the present survey was to provide a literary review of current knowledge of the possible association between the psychosocial working environment and relevant physiological parameters measured in blood and urine. Literature databases (PubMed, Toxline, Biosis and Embase) were screened using the key words job, work-related and stress in combination with selected physiological parameters. In total, 51 work place studies investigated the associations between the psychosocial working environment and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 91 publications
6
64
0
Order By: Relevance
“…Additionally, we obtained serum concentrations of glycated hemoglobin (HbA 1c ) and testosterone as markers of catabolic and anabolic processes, respectively (Hansen et al 2009). As testosterone exhibits diurnal variation, which may be aVected by night work, we excluded participants (baseline, n = 5; follow-up, n = 2), who indicated that they worked night shifts from the analyses of testosterone.…”
Section: Reference Groupmentioning
confidence: 99%
“…Additionally, we obtained serum concentrations of glycated hemoglobin (HbA 1c ) and testosterone as markers of catabolic and anabolic processes, respectively (Hansen et al 2009). As testosterone exhibits diurnal variation, which may be aVected by night work, we excluded participants (baseline, n = 5; follow-up, n = 2), who indicated that they worked night shifts from the analyses of testosterone.…”
Section: Reference Groupmentioning
confidence: 99%
“…There is a slight diurnal variation in both sexes and testosterone is highest in the morning after a good nights sleep [9]. Testosterone has been shown to be a good biomarker for adverse psychosocial working environment for both men and women [21].…”
Section: Introductionmentioning
confidence: 98%
“…It has been used as a measure of glycemic control among diabetic patients, as well as a possible screening test for undetected DM (Lippi and Targher 2010). Several studies have reported that stressful working conditions were associated with increased concentrations of HbA1c in non-diabetic populations (Cesana et al 1985;Kawakami et al 1989Kawakami et al , 2000Feldman and Steptoe 2003;Grossi et al 2003;Hansen et al 2009). However, all the studies were conducted in developed countries, in which job stress was evaluated by job demand-control-support model.…”
Section: Introductionmentioning
confidence: 99%